Young people pursuing futures: making identity labors curricular. (3rd April 2021) - Zipin, Lew; Brennan, Marie; Sellar, Sam
ABSTRACT: Young people's processes of forming identities, linked to the work of anticipating futures, involve significant labors of thought, feeling, ethics and imagination. These labors proceed across both life-worlds and school-worlds, often in tension, especially for those from marginalized positions in social-structural power relations. This paper explores such identity labors, drawing on rich ethnographic data from research, during 2013–2014, that engaged students in Years 9 and 10, from working-class, immigrant and refugee backgrounds, who attended an inner-suburban school in Melbourne, Australia. We investigate two student groupings: (a) selected by the school for "accelerated" curriculum paths; and (b) the "others" we label written off by the school in terms of academic potential (a division we diagnose as driven by policy measures of institutional "performance"). In different ways among students in each grouping, we find their identity labors to reflect historical conditions for what Berlant calls "cruel optimism" about futures. Yet their identity dynamics also draw on rich funds of knowledge from their life-worlds that our research shows to offer resources – funds of identity – for more viable future imaginaries. We argue for curriculum and pedagogy that supports young people in their identity labors to live from their present into emergent, new-generational futures.